Legal Study of Stolen Property Collectors and Their Legal Effects According to the Criminal Code - Barmawi, Ahmad; Hakim, Abdul; Jannah, Maya (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The purpose of this study is to know about the Application of Legal Sanctions against stolen goods collectors according to the Criminal Code. The research method used in this writing is Normative Law research. Results of Discussion: Application of legal sanctions against the criminal act of possession of stolen goods in accordance with the provisions of Article 480 of the Criminal Code by fulfilling the following elements: a) Whose goods, defined as a person or perpetrator of the procurement of goods; b) Buying goods, defined as the act of purchasing goods where the goods are the result of a crime. c) It is appropriate or known and suspected that the goods obtained from the act of crime, means that it is appropriate for the buyer to have a suspicion that the goods purchased are the proceeds of crime. The judge's consideration in determining the responsibility of the perpetrator of the prosecution through the evidentiary power of legal evidence. The legal evidence used is the proceeds of crime, witness statements, expert witnesses, letters and statements of the accused. Legal sanctions for the container of stolen goods are punishable by imprisonment for a maximum of 4 (four) years or a maximum fine of Rp.900,- (nine hundred rupiah). However, the holder of stolen goods in the light category, as mentioned in Article 482 of the Criminal Code, has a maximum penalty of three months or a maximum fine of Rp. 900,- (nine hundred rupiah).